Meningkatkan Kemampuan Memukul Bola dengan Stand Up Ball pada Pembelajaran Softball bagi Siswa SD Muhammadiyah Sapen Yogyakarta - Sudaryono, Agung (Jurnal Didaktika Pendidikan Dasar, 2024)
The purpose of this study is to find out the improvement of softball hitting skills for grade IV students of Al Jazari Muhammadiyah Sapen Elementary School Yogyakarta with a stand up ball aid as a substitute for a Pitcher Machine. The type of research used is the Miles and Hubberman model Classroom Action Research with two cycles and three stages, namely planning, implementation and observation and reflection. Data were obtained from performance assessments and observations by researchers and collaborators during learning. The research instruments used pitched ball tests, and observation sheets for teachers and students. The data was processed with a qualitative descriptive analysis model. Of the 29 research subjects when the pitched ball test was carried out, it was found that in cycle 1 a score of 54 strikes was obtained and in cycle 2 a score of 74 strikes or an increase of 85%. Qualitatively the results showed that it was easier for the subjects to learn to hit a softball from a stationary position (static) and then learn to hit a moving ball (dynamic), with the softball hitting tool felt more fun and more challenging and an increase in the technical score of the results in the obervation from 74 to 84. It is necessary to further investigate the existence of two students because there is no improvement in ability at all.